HUBUNGAN PEKERJAAN DAN SIKAP IBU MENYUSUI DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI DESA LEBENG TIMUR KECAMATAN PASONGSONGAN - Nelyta Oktavianisya; Sri Sumarni (Fakultas Ilmu Kesehatan, 2017)
Breastfeeding is a natural process but often mothers fail to breastfeed more than theyshould. Lots of moms who choose not to give Exclusive Breast Milk. The problem of this research isthe low level of Exclusive Breastfeeding in Lebeng Timur Village Pasongsongan Sub-district by4.5% from the target of 90%. The aim of this research is to determine the relationship between jobsand mother attitude with giving of exclusive ASI in Lebeng Timur Village Pasongsongan SubDistrict.The design of this study is Cross Sectional Study. The sample sum a 40 nursing mothers whohave infants aged> 6-12 months taken using proportionate random sampling technique. The dataanalyzed using Chi- square test.The results showed that some of the respondents work (65%), had positive attitude (47,5%),and only (37,5%) respondents give exclusive breastfeeding. There is a relation between jobs(p=0.000) and the attitude of the breastfeeding mother (p=0,012) whit the exclusive breastfeeding.Mothers, particularly career mothers, are suggested to always give breast milk so that they couldpromote to the success of exclusive breastfeeding.